Theoretical and harmonic analysis of magnetic fields in the active zone of a turbogenerator under load conditions - V.I. Milykh (National Technical University "Kharkiv Polytechnic Institute", 2013)
The paper presents some principles and results of numerical field calculation and the corresponding harmonic analysis of magnetic field in the active zone of a large turbogenerator under load conditions. In addition to the traditional coordinate function of the magnetic induction, its time functions are considered at fixed points and at rotating rotor linked points in the gap. The stator magnetic flux linkage functions are also examined. It is revealed that these magnetic induction functions, which are different from sine curves, fail to provide the basis for determining time functions of magnetic flux linkage and the stator winding EMF that are close to sine waves.